RFID Security A Lightweight Paradigm - Khattab, Ahmed; Jeddi, Zahra; Amini, Esmaeil; Bayoumi, Magdy; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2017)
This book provides a comprehensive treatment of security in the widely adopted, Radio Frequency Identification (RFID) technology. The authors present the fundamental principles of RFID cryptography in a manner accessible to a broad range of readers, enabling them to improve their RFID security design. This book also offers the reader a range of interesting topics portraying the current state-of-the-art in RFID technology and how it can be integrated with today's Internet of Things (IoT) vision. The authors describe a first-of-its-kind, lightweight symmetric authenticated encryption cipher called Redundant Bit Security (RBS), which enables significant, multi-faceted performance improvements compared to existing cryptosystems. This book is a must-read for anyone aiming to overcome the constraints of practical implementation in RFID security technologies.
Part I. RFID Security Preliminaries -- 1. Introduction to RFID -- 2. RFID Security Threats and Basic Solutions -- 3. Cryptography in RFID Systems -- Part II. Lightweight RFID Redundant Bit Security -- 4. RBS Cryptosystem -- 5. RBS Security Analysis -- 6. RBS Performance Evaluation -- 7. RBS RFID Security and The Internet of Things.
Keywords: Electronic circuits; Microprocessors; Computer architecture; Signal processing; Electronic Circuits and Systems; Processor Architectures; Signal, Speech and Image Processing